KÜRESEL MARKALARIN YEREL PAZARLARDAKİ REKLAM STRATEJİLERİ İLE KÜLTÜREL FARKLILIKLAR ARASINDAKİ İLGİ ÜZERİNE BİR UYGULAMA - (:unkn) unknown (My University, 2016)
Küreselleşme ile birlikte artan küresel rekabet ortamı işletmeleri küresel marka yaratmaya yönlendirmektedir. Küresel markaların yerel pazarlarda uygulayacağı reklam stratejileri ise bu rekabette başarılı olabilmek için önemlidir. Küresel markaların başarısı veya başarısızlığı tüketicilere yani insanlara da bağlı olduğundan, insan hayatının önemli bir parçası olan kültür bu noktada dikkate alınması gereken bir unsur olarak ortaya çıkmaktadır.Bu çalışmanın amacı küresel markaların yerel pazarlarda reklam stratejisi uygularken kültürel farklılıkları dikkate alıp almadığını, yani aralarındaki ilgiyi incelemektir. Bu doğrultuda uygulama bölümünde beş küresel markanın Türkiye pazarında yayınlanmış televizyon reklamları incelenerek, uyguladıkları reklam stratejilerinde kültürel farklılıkların dikkate alınıp alınmadığı, Hofstede'in kültürel farklılıkları gösteren dört öğesi (semboller, kahramanlar, ritüeller, değerler) ile karşılaştırılarak değerlendirilmiştir

Globalization, along with an increase in the global competitive environment is direction in the business to create a global brand. Advertising strategies that is appointed by global brands in local markets and its success in this competition is very important. Success or failure of global brands are connected to consumers, people and the culture as an important part of life has to be taken into account at this point and it seems as a major factor.The purpose of this study is to find out to what extend global brands takes cultural differences into account in its advertising strategy when it applies them in the local markets and at the same time to investigate the relationship between them. In this regard, the practical part of five global brands examined published television commercials in Turkey's market, advertising strategies implemented by taken into account cultural differences, the four elements, showing Hofstede's cultural differences (symbols, heroes, rituals, values) are compared and evaluated
AN APPLICATION OF THE RELATION BETWEEN THE ADVERTISING STRATEGIES OF GLOBAL BRANDS ON LOCAL MARKETS AND CULTURAL DIFFERENCES